The tailoring of competition policy to Caribbean circumstances : some suggestions - Dhanjee, Rajan (2004)
Provides an overview of the benefits and objectives of competition policy, and different approaches to it in different jurisdictions. Suggests how competition policy might be applied in the Caribbean, covering both some substantive and institutional aspects.